American, Soviet, British, Polish and Japanese Views on the Future Status of Eastern Europe and, in Particular, of Hungary (Text and References) - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution.